Analisa Perbandingan Kinerja Routing Ripv1 Eigrp Dan Ospf Di PT. Chevron Pacific Indoneisa - Ramdhani Syahputra; Linna Oktaviana; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The company that has business units specific location would want the business units are connected to one another in a network and can share important information quickly to support the company's business continuity. One is seeking a fast network connection to send the shipment and demand data. One solution that can be used is the routing protocol. The use of routing protocols greatly affect how network performance local area network of a company. To support LAN network performance optimization, routing protocols have a fundamental role in the network. Selection of the appropriate routing protocols necessary for optimal and efficient network, and can cope with complex routing situations quickly and accurately. Case studies conducted in PT.Chevron Pacific Indonesia to implement multiple routing protocols on the LAN network PT.Chevron Pacific Indonesia. Implementers conducted in simulated General Network Simulator 3 and use wireshark to get a delay, packet loss, and thrpoughput using Open Shortest Path First routing, Routing Information Protocol version 1, and Enchanced Interior Gateway Routing Protocol for LAN network PT.Chevron Pacific Indonesia. The results of this simulation design obtained QOS routing OSPF, RIPv1, and EIGRP, and OSPF routing is obtained that has the best performance seen from the measured parameters.Keyword : Routing Protokol, OSPF, EIGRP, RIP, QOS